2015
DOI: 10.1177/0003489415588130
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Selection for T3/T4a Laryngeal Cancer

Abstract: Through careful selection, some patients with locally advanced laryngeal cancer can be offered chemoradiation (organ preservation) without compromising survival. However, the patients selected to receive chemoradiation have a high rate of laryngeal and esophageal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 13 publications
2
46
1
6
Order By: Relevance
“…Table summarizes a literature review of the different therapeutic options. In several studies of surgical treatments, including total laryngectomy, the 5‐year OS rates ranged from 41% to 85.5% . Although it is difficult to compare these earlier results directly with our findings, the survival rates in our study tended to be favorable.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Table summarizes a literature review of the different therapeutic options. In several studies of surgical treatments, including total laryngectomy, the 5‐year OS rates ranged from 41% to 85.5% . Although it is difficult to compare these earlier results directly with our findings, the survival rates in our study tended to be favorable.…”
Section: Discussionsupporting
confidence: 52%
“…In several studies CRT, respectively, thereby demonstrating that CRT is a more favorable treatment for patients with T2b relative to RT alone 30. In a recent study of LP, Timme et al calculated a 2-year LEDFS rate of 40% in patients with T3 disease treated with IV-CRT 24. Fuller et al reported 5-year LFS rates of 38% and 62% in patients with T3 disease treated with definitive RT or systemic CRT, respectively, and 5-year LEDFS rates of 37% and 59% in patients with T3 disease treated with definitive RT or systemic CRT, respectively 25.…”
mentioning
confidence: 99%
“…In fact, when dealing with anterior T3 tumors with normal vocal cord/arytenoid mobility (subcategory I), OPHL compares favorably with transoral laser microsurgery (TLM; whose local control has been shown to be in the range of 44%-72% for glottic and 70%-87% for supraglottic tumors), [24][25][26][27] and with CRT (whose 2-year laryngoesophageal dysfunction-free survival has been reported to be around 40%). 28 The inner thyroid lamina infiltration does not negatively impact on the possibility to attain adequate disease control by such an open-neck conservative approach, although this is definitely the case for TLM and the issue is still debated for CRT.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, comparing CRT versus primary surgery, Timme et al 28 showed that some selected patients with locally advanced laryngeal cancer can be offered nonsurgical organ preservation without compromising survival. However, these have higher rates of laryngeal and esophageal dysfunction than those obtained by OPHLs.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to administer a complete treatment regimen can be multifactorial, in which the patient's performance status at the inception of treatment, nutritional status and support before and during treatment, the skill and experience of the treating team with the appropriate selection of patients for organ preservation, and the management of side effects and complications are important factors to consider. [16][17][18] If the team is inexperienced or unwilling to complete the regimen due to fear of complications, patients will be undertreated. In addition, acute toxicity experienced during CRT would play a major role in treatment incompletion.…”
Section: Discussionmentioning
confidence: 99%